Discovery of the First Aphid-Infecting Nudiviruses Reveal Bidirectional Host-Virus Gene Transfer - Cubillos-Riffo, F (Academic Press, 2025)
Nudiviruses are double-stranded DNA viruses that infect invertebrate species, ranging from aquatic arthropods to insects from diverse orders. Remnants of nudiviral infections have been found as introgressions in the genome of several insect hosts, such as aphids pest species (Hemiptera: Aphididae). However, a nudivirus infecting aphids has yet to be reported. Here, we describe the complete genome sequences of two nudiviruses found in the aphid Neuquenaphis staryi, a species that branched out early in the Aphididae family and is endemic to southern beech forests in South America. These nudiviruses (NsNV-1 and NsNV-2) share 98% of nucleotide identity between them and belong to the Alphanudivirus genus. Notably, we found that the prevalence of NsNV-1 was 16 times higher than NsNV-2 in natural N. staryi populations, and co-infections were not observed. Furthermore, we show that horizontal gene transfer between aphids and nudiviruses has been bidirectional, providing evidence of their dynamic co-evolutionary relationship. This study provides the first documentation of nudivirus infections in aphids and expands our understanding of the evolutionary interactions between nudiviruses and their insect hosts. © 2025 Elsevier Inc.